Supination/pronation movement quantification using stereoscopic vision based system towards Parkinson's Disease assessment – A pilot study. (July 2020) - Vaz, Pedro G.; Reis, Ana L.; Cardoso, João
Abstract: Parkinson's disease is a neurodegenerative disorder that degrades the motor performance of patients. Specific motor symptoms, including tremor and bradykinesia, are clinically evaluated through the Unified Parkinson's disease Rating Scale (UPDRS), but with limited reproducibility and accuracy due to its intrinsic qualitative nature. A free-field and non-contact movement assessment method, based on stereoscopic imaging (Leap Motion controller) has been explored to precisely quantify supination/pronation (SUPRO) hand movements. A bench experiment was designed using a hand phantom to test its linearity. The Leap Motion controller presented a linear response considering rotation angles from −45° to 45° ( r 2 = 0.995). A serious game was developed to guide the data acquisition procedure, with a protocol similar to that of UPDRS, in 31 healthy subjects. The SUPRO hand movement was characterized in terms of root mean square values, predominant frequency, total spectral power and number of zero crossings. The control group achieved root mean square values of 9.60 ± 2.87 rad/s, a predominant frequency of 2.43 ± 0.52 Hz, a total spectral power of 927 ± 571 (rad/s) 2 and a number of zero crossings of 275 ± 101. Also, a patient with Parkinson's disease was tested with a similar fashion, obtaining significantly different parameters.